Income Redistribution in a Common Labor Market - Wildasin, David E. (American Economic Review, 1991)
When households are mobile among jurisdictions, income redistribution by individual jurisdictions creates fiscal externalities. A model of interjurisdictional migration is used to study the nature of this redistributive externality. Analysis of optimal redistribution and optimal corrective subsidies from higher-level governments shows that benefit levels for the recipients of income transfers and tax rates on mobile taxpayers should be equalized across jurisdictions. A system of jurisdictions with a common labor market can achieve welfare improvements through coordination of "domestic" redistributive policy or through the intervention of a higher-level government.